Pathway of effects of adverse childhood experiences on the poly-drug use pattern among adults using drugs: A structural equation modeling - Li, Jing; He, Jianhui; Wang, Pei; Li, Jiashuang; Zhang, Yunjia; You, Jing; Chongsuvivatwong, Virasakdi (Frontiers in Public Health, 2023)
Background: Polydrug abuse could result in negative health outcomes, and adverse childhood experiences (ACEs) are associated with an increased risk of substance use. However, evidences on direct relationship between ACEs and polydrug use are still lacking. We explored the associations between ACEs and polydrug use by structural equation models (SEM). Methods: A cross-sectional study was conducted among border drug use adults in China’s southwest border in 2021. SEM was used to explore the relationship between ACEs and polydrug use in adulthood. Results: The study included 406 subjects with an average of 34 years old who were majorities of males (399), minorities (323), unmarried (71.7%), and employed (81.3%). Majorities used alcohol (91.6%) and had ACEs (95.5%). The average friend drug use, self-perception of drug abuse, and drug use scores were 1.0, 8.0, and 1.0, respectively. The correlation analysis of variables used in SEM showed that age was negatively related to income, drinking status and frequency of drug use (β=0.496), ACEs (β=0.109) and income (β=0.094) were possible risk factors for polydrug use while self-perception of drug abuse was a possible protective factor (β=0.083). Conclusions: ACEs could be a direct or indirect risk predictor for the development of polydrug use in adulthood as well as friend drug use and monthly income.